Amplification of Dissymmetry Factors in π-Extended [7]- and [9]Helicenes - Qiu, Zijie (J Am Chem Soc, 2021)
[Image: see text] π-Extended helicenes constitute an important class of polycyclic aromatic hydrocarbons with intrinsic chirality. Herein, we report the syntheses of π-extended [7]helicene 4 and π-extended [9]helicene 6 through regioselective cyclodehydrogenation in high yields, where a “prefusion” strategy plays a key role in preventing undesirable aryl rearrangements. The unique helical structures are unambiguously confirmed by X-ray crystal structure analysis. Compared to the parent pristine [7]helicene and [9]helicene, these novel π-extended helicenes display significantly improved photophysical properties, with a quantum yield of 0.41 for 6. After optical resolution by chiral high-performance liquid chromatography, the chiroptical properties of enantiomers 4-P/M and 6-P/M are investigated, revealing that the small variation in helical length from [7] to [9] can cause an approximately 10-fold increase in the dissymmetry factors. The circularly polarized luminescence brightness of 6 reaches 12.6 M(–1) cm(–1) as one of the highest among carbohelicenes.